Lithium ion battery composite negative electrode material and preparation method and application thereof

By combining carbon nanotubes with scandium nitride and using steps such as acidification and high-temperature heat treatment, scandium nitride/carbon nanotube composite materials are prepared, which solves the problem of volume expansion of the negative electrode material of lithium-ion battery after cyclic charging and discharge, and achieves high capacity, high stability and good conductivity, which is suitable for commercial applications.

CN119890281APending Publication Date: 2025-04-25LIYANG TIANMU PILOT BATTERY MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311381386.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-24
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The existing lithium-ion battery anode materials have volume expansion problems after cyclic charging and discharging, resulting in poor material powdering and electrochemical performance, and lack of commercially applicable composite anode materials that perform excellent in chemical stability, conductivity and capacity.

Method used

Scandium nitride/carbon nanotube composite materials are prepared by combining carbon nanotubes with scandium nitride, acidification treatment and high-temperature heat treatment, etc., to improve the conductive properties and electrochemical stability of the material and alleviate the problem of volume expansion.

Benefits of technology

It achieves high capacity, high stability and good conductivity, extends the cycle life of the battery, and is suitable for large-scale industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119890281A_ABST
    Figure CN119890281A_ABST
Patent Text Reader

Abstract

The embodiment of the invention relates to a lithium ion battery composite negative electrode material and a preparation method and application thereof. The preparation method comprises the following steps: putting carbon nanotube powder into a flask, adding an acidic solution to acidize the carbon nanotube powder, and performing condensation reflux treatment in a constant-temperature oil bath pan to remove surface impurities and oxides; carrying out centrifugal solid-liquid separation on the condensed liquid, washing and drying, dispersing the condensed liquid and scandium metal salt into an organic solvent or water together, and carrying out ultrasonic treatment to obtain a mixed solution; adding an organic ligand into the mixed solution, continuously stirring until the reaction is complete, collecting a precipitate through centrifugal solid-liquid separation, washing and drying to obtain a scandium nitride / carbon nanotube composite material precursor; the organic ligand comprises at least one of dimethylimidazole, ethylenediamine tetraacetic acid or ethylenediamine; and performing high-temperature heat treatment on the scandium nitride / carbon nanotube composite material precursor in an inert atmosphere, and cooling to room temperature to obtain the scandium nitride / carbon nanotube composite material, namely the lithium ion battery composite negative electrode material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of nano energy materials, and in particular to a lithium ion battery composite negative electrode material and a preparation method and application thereof. Background Art

[0002] With the construction of modern energy system, clean energy has become a hot research topic. Based on this, energy storage and conversion equipment has emerged. Lithium-ion batteries have become the core device in the new energy revolution due to their high energy density and long service life. As a key component of lithium-ion batteries, the performance of negative electrode materials plays a vital role in the energy density, power density, cycle stability and safety of lithium-ion batteries.

[0003] Carbon nanotubes (CNTs) have a graphite-like layered structure. This special microscopic morphology makes the embedding of lithium ions more efficient during the charge / discharge process, and the material has high cycle efficiency and long cycle life. At the same time, carbon nanotubes have excellent electrical conductivity and good electron conduction and ion transmission capabilities, making them the first choice for negative electrode materials for lithium-ion batteries. However, there are also some disadvantages in using carbon nanotubes directly as negative electrode materials, such as relatively low initial charge and discharge efficiency, potential hysteresis, and poor voltage stability.

[0004] In order to improve the electrochemical performance of carbon nanotubes, carbon nanotubes can be compounded with other materials.

[0005] Commonly used negative electrode materials composited with carbon nanotubes include:

[0006] 1. Graphite: Graphite is a traditional negative electrode material for lithium-ion batteries. Combining it with carbon nanotubes can improve battery performance, such as increasing capacity and reducing solid-liquid interface resistance.

[0007] 2. Silicon: Silicon has high capacity, but it is prone to expansion and contraction during the charge and discharge process, leading to the cracking of electrode materials. Carbon nanotubes can be used as a skeleton material to help stabilize silicon particles and reduce damage caused by expansion.

[0008] 3. Metal Oxides: Metal oxides such as tin oxide and titanium dioxide are often compounded with carbon nanotubes to increase battery capacity and improve electrical conductivity.

[0009] 4. Silicon Carbide (SiC): Silicon carbide is a material that is resistant to high temperatures and chemical corrosion. When combined with carbon nanotubes, it can improve the stability of the battery.

[0010] These carbon nanotube composites can improve the performance of lithium-ion batteries by increasing the conductivity of electrode materials, reducing solid-liquid interface resistance, and increasing the stability of materials.

[0011] However, there is still a lack of a commercially applicable composite negative electrode material that excels in chemical stability, conductivity, capacity, etc. Summary of the invention

[0012] The purpose of the present invention is to provide a composite negative electrode material for lithium-ion batteries, a preparation method and an application thereof. The composite negative electrode material can effectively alleviate the volume expansion after cyclic charge and discharge, and prevent the pulverization of the composite negative electrode material; at the same time, it can also improve the conductivity of the composite negative electrode material and improve the electrochemical performance of the composite negative electrode material. The negative electrode material synthesized by the present invention has good reversible capacity, first coulomb efficiency and cycle stability, and the preparation method is simple and suitable for large-scale industrial production.

[0013] To this end, in a first aspect, an embodiment of the present invention provides a method for preparing a composite negative electrode material for a lithium ion battery, the preparation method comprising:

[0014] Placing carbon nanotube powder in a flask, adding an acidic solution to acidify the carbon nanotube powder, and performing condensation reflux treatment in a constant temperature oil bath at 90-130° C. to remove impurities and oxides on the surface of the carbon nanotube powder material; performing centrifugal solid-liquid separation on the condensed liquid after the condensation reflux treatment, washing the separated solid powder with deionized water and ethanol respectively, and drying the solid material obtained after washing in an oven to obtain pretreated carbon nanotubes;

[0015] Weighing the scandium metal salt and the pretreated carbon nanotubes, dispersing them into an organic solvent or water, and uniformly mixing them by ultrasonication to obtain a mixed solution;

[0016] Adding an organic ligand to the mixed solution and continuously stirring until the reaction is complete, collecting a precipitate by centrifugal solid-liquid separation, washing the precipitate with deionized water and ethanol respectively, and drying the solid material obtained after washing in an oven to obtain a scandium nitride / carbon nanotube composite material precursor; wherein the organic ligand comprises at least one of dimethylimidazole, ethylenediaminetetraacetic acid or ethylenediamine;

[0017] The scandium nitride / carbon nanotube composite material precursor is subjected to high temperature heat treatment at 600° C.-900° C. in an inert atmosphere, and after cooling to room temperature, a scandium nitride / carbon nanotube composite material is obtained, which is the lithium ion battery composite negative electrode material.

[0018] Preferably, the acidic solution includes one or more of concentrated nitric acid, concentrated hydrochloric acid, and concentrated sulfuric acid;

[0019] The liquid-to-solid ratio of the acidic solution to the carbon nanotubes is 50-150 mL / g.

[0020] Preferably, the condensation reflux treatment time is 10-12 hours.

[0021] Preferably, the rotation speed of the centrifugal solid-liquid separation is 5000rpm-8000rpm, and the time is 10min;

[0022] The washing with deionized water and ethanol respectively specifically includes: washing with ethanol and deionized water alternately three times.

[0023] Preferably, the scandium metal salt includes: one or more of scandium chloride, scandium nitrate, scandium sulfate, scandium oxalate and hydrates thereof;

[0024] The mass ratio of the scandium metal salt to the pretreated carbon nanotubes is 1:10-1:20;

[0025] The organic solvent includes: at least one of methanol, ethanol, ethylene glycol, and N,N-dimethylformamide;

[0026] The ratio of the total mass of the scandium metal salt and the pretreated carbon nanotubes to the volume of the organic solvent or water is 1 g / 100 mL to 10 g / 100 mL;

[0027] The ultrasonic time is 0.5-1h.

[0028] Preferably, the mass ratio of the scandium metal salt to the organic ligand is 1:4-1:10.

[0029] Preferably, the inert atmosphere is nitrogen or argon;

[0030] During the heating process of the high-temperature heat treatment, the heating rate is 2°C / min-10°C / min; and the heat treatment time is 2h-8h.

[0031] In a second aspect, an embodiment of the present invention provides a lithium-ion battery composite negative electrode material prepared by the preparation method described in the first aspect.

[0032] In a third aspect, an embodiment of the present invention provides a lithium battery negative electrode plate, comprising the lithium ion battery composite negative electrode material described in the second aspect above.

[0033] In a fourth aspect, an embodiment of the present invention provides a lithium battery, comprising the lithium battery negative electrode plate described in the third aspect above.

[0034] The preparation method of the lithium-ion battery composite negative electrode material provided by the embodiment of the present invention can not only further improve the electrochemical performance of the composite negative electrode material, alleviate the potential problems of single-phase carbon nanotubes or transition metal nitrides in the use process, such as low rapid charge and discharge efficiency, potential hysteresis, poor voltage stability, volume expansion, etc., but also is expected to obtain a lithium battery negative electrode material with high capacity, high stability and commercial application. The materials used in the preparation method provided by the embodiment of the present invention are low-cost and easy to obtain. In the process of preparing the electrode material, the operation is simple, the process time is short, and it is suitable for large-scale industrial development. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 The present invention provides a flow chart of a method for preparing a composite negative electrode material for a lithium-ion battery. DETAILED DESCRIPTION

[0036] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments.

[0037] The present invention provides a method for preparing a composite negative electrode material for a lithium-ion battery. The main steps are as follows: Figure 1 As shown, the preparation method comprises:

[0038] Step 110, placing the carbon nanotube powder in a flask, adding an acidic solution to acidify the carbon nanotube powder, performing condensation reflux treatment in a constant temperature oil bath at 90-130° C., and removing impurities and oxides on the surface of the carbon nanotube powder material; performing centrifugal solid-liquid separation on the condensed liquid after the condensation reflux treatment, washing the separated solid powder with deionized water and ethanol respectively, and drying the solid material obtained after washing in an oven to obtain pretreated carbon nanotubes;

[0039] Specifically, the acidic solution includes one or more of concentrated nitric acid, concentrated hydrochloric acid, and concentrated sulfuric acid; wherein concentrated nitric acid generally refers to nitric acid with a molar concentration of more than 16 mol / L, concentrated hydrochloric acid refers to hydrochloric acid with a molar concentration of more than 10 mol / L, and concentrated sulfuric acid refers to sulfuric acid with a molar concentration of more than 18 mol / L.

[0040] The liquid-to-solid ratio of the acidic solution to the carbon nanotubes is 50-150 mL / g.

[0041] In addition to removing surface impurities and oxides, acid treatment can also introduce functional groups through acid treatment, so that the surface of carbon nanotubes undergoes functional modification, making it easier to chemically react with other substances (such as organic ligands or metal ions) to form composite materials. In addition, acid treatment helps to improve the dispersibility of carbon nanotubes in solution, making it easier to disperse in organic solvents or water, thereby providing better conditions for subsequent reaction steps.

[0042] In summary, the addition of acidic solution to the acidification of carbon nanotubes is a key step, which can improve the purity, surface quality and chemical activity of carbon nanotubes, and provide more favorable conditions for subsequent material preparation steps. This treatment helps to improve the interaction between carbon nanotubes and other substances, thereby generating the desired composite materials.

[0043] The condensation reflux treatment time is 10-12h.

[0044] The speed of centrifugal solid-liquid separation is 5000rpm-8000rpm, and the time is 10min;

[0045] The washing with deionized water and ethanol respectively is specifically performed by using ethanol and deionized water to wash alternately three times.

[0046] The drying temperature is preferably 80°C.

[0047] Step 120, weighing the scandium metal salt and the pretreated carbon nanotubes, dispersing them into an organic solvent or water, and mixing them uniformly by ultrasonication to obtain a mixed solution;

[0048] Specifically, the scandium metal salt includes: one or more of scandium chloride, scandium nitrate, scandium sulfate, scandium oxalate and hydrates thereof; the mass ratio of the scandium metal salt to the pretreated carbon nanotubes is 1:10-1:20.

[0049] The organic solvent includes at least one of methanol, ethanol, ethylene glycol and N,N-dimethylformamide; the ratio of the total mass of the scandium metal salt and the pretreated carbon nanotubes to the volume of the organic solvent or water is 1g / 100mL-10g / 100mL.

[0050] The ultrasound time is 0.5-1h.

[0051] Step 130, adding an organic ligand to the mixed solution and continuously stirring until the reaction is complete, collecting a precipitate by centrifugal solid-liquid separation, washing the precipitate with deionized water and ethanol respectively, and drying the solid material obtained after washing in an oven to obtain a scandium nitride / carbon nanotube composite material precursor;

[0052] Among them, organic ligands include dimethylimidazole (C5H8N2), ethylenediaminetetraacetic acid (EDTA, C10 H 16 N2O8) or ethylenediamine (C2H8N2) at least one.

[0053] The drying temperature is preferably 80°C.

[0054] In this step, the scandium metal salt reacts with ligands such as dimethylimidazole, ethylenediaminetetraacetic acid or ethylenediamine to form a corresponding scandium ion complex. The chemical formula of the specific complex generated will vary depending on the type and coordination number of the ligand. The following are some examples of possible complexes:

[0055] Scandium ions react with dimethylimidazole to form [Sc(C5H8N2) x ] (3-x)+ , where x can vary depending on the coordination number.

[0056] Scandium ions react with ethylenediaminetetraacetic acid (EDTA) to form [Sc(EDTA)] - .

[0057] Scandium ions react with ethylenediamine to form [Sc(C2H8N2) x ] (3-x)+ , where x can vary depending on the coordination number.

[0058] The purpose of this step is to form a metal-organic complex precursor by introducing metal ions and organic ligands.

[0059] Step 140 , subjecting the scandium nitride / carbon nanotube composite material precursor to a high temperature heat treatment at 600° C.-900° C. in an inert atmosphere, and cooling it to room temperature to obtain a scandium nitride / carbon nanotube composite material, which is a composite negative electrode material for lithium-ion batteries.

[0060] Specifically, the inert atmosphere is nitrogen or argon;

[0061] During the high temperature heat treatment, the heating rate from room temperature to the heat treatment temperature is 2°C / min-10°C / min; the heat treatment time is 2h-8h. The metal organic complex decomposes during the heat treatment to generate scandium nitride and other gaseous products.

[0062] The present invention takes into account the special physical and chemical properties of transition metal nitrides. Since nitrogen atoms occupy the metal lattice, the metal lattice expands, the unit cell constant increases, the interaction between metal atoms weakens, the d-band filling state shrinks and narrows, the state density near the Fermi level is redistributed, and the electronic structure is adjusted. Therefore, the material has the characteristics of high mechanical strength, stable chemical properties, and good electrical conductivity. Therefore, by compounding scandium nitride with carbon nanotubes, a lithium battery negative electrode material with high capacity, high stability and commercial application can be obtained.

[0063] The composite material prepared by the preparation method of the embodiment of the present invention can be used as a negative electrode material for lithium-ion batteries and applied to lithium battery pole pieces and lithium batteries.

[0064] Composites of carbon nanotubes and scandium nitride have several potential advantages in lithium-ion batteries, including:

[0065] The combination of the two can improve the overall conductivity of the electrode, reduce the internal resistance of the battery, and thus improve the charging and discharging performance of the battery.

[0066] Scandium nitride has a higher capacity and can store more lithium ions. By compounding with carbon nanotubes, the structural stability of the material can be better maintained, reducing damage caused by capacity expansion and contraction, thereby improving the energy storage capacity of the battery.

[0067] Scandium nitride has good chemical stability and can reduce adverse reactions between electrode materials and electrolytes. The protective effect of carbon nanotubes helps to further enhance the stability of electrode materials and extend the life of the battery.

[0068] Carbon nanotubes have excellent electrical conductivity and can facilitate rapid charge transport, thereby increasing the charging speed of the battery.

[0069] The composite of nanotubes and scandium nitride helps to reduce the solid-liquid interface resistance between the battery electrode and the electrolyte, thereby improving the efficiency and power density of the battery.

[0070] The materials used in the preparation method provided by the embodiment of the present invention are low-cost and easily available. In the process of preparing the electrode material, the operation is simple and the process time is short, which is suitable for large-scale industrial development.

[0071] In order to more clearly illustrate the purpose and advantages of the present invention, the present invention is further described below in conjunction with the embodiments. In addition, the embodiments described in the present invention are only partial embodiments. Based on the embodiments described in the present invention, all other embodiments obtained by those skilled in the art without creative work are within the protection scope of the present invention. In addition, it should be understood that these embodiments are only used for more detailed description and should not be understood as limiting the present invention in any form, that is, they are not intended to limit the protection scope of the present invention.

[0072] Example 1

[0073] This embodiment provides a method for preparing a composite negative electrode material for a lithium-ion battery and a performance test thereof. The specific preparation process is as follows.

[0074] Weigh 15g of carbon nanotube powder and place it in a round-bottom flask. Slowly add concentrated sulfuric acid solution at a solid-liquid ratio of 150mL / g. Perform condensation reflux treatment in a constant temperature oil bath at 130℃ for 10h. Acidification of carbon nanotubes can effectively remove impurities and oxides on the surface of the material and improve the purity of the material. Use a centrifugal speed of 8000rpm and a centrifugal time of 10min to separate the solid and liquid. Then wash the solid carbon nanotube powder with deionized water and ethanol three times. Place the obtained solid in an oven and dry it at 80℃ to obtain acid-treated carbon nanotubes. Weigh 10g of acidified carbon nanotubes and 1g of scandium nitrate and disperse them in 110mL of ethanol solution. Ultrasonicate for 1h to mix evenly to obtain a mixed solution. 4 g of dimethylimidazole was added to the mixed solution, and the mixture was stirred continuously until the reaction was complete. The mixture was centrifuged at 8000 rpm for 10 min, and the precipitate was collected and washed three times with deionized water and ethanol. The obtained solid was placed in an oven and dried at 80°C to obtain a scandium nitride / carbon nanotube composite material precursor. The precursor was heated to 900°C at a heating rate of 2°C / min in a nitrogen atmosphere, and heat-treated for 2 h. After cooling to room temperature, a scandium nitride / carbon nanotube composite material was obtained.

[0075] The prepared negative electrode material was used to prepare a negative electrode sheet and a button-type half-cell was assembled for testing. The specific process is as follows.

[0076] The prepared lanthanum-doped tin-based negative electrode material was weighed with conductive carbon black, sodium carboxymethyl cellulose and styrene-butadiene rubber in a mass ratio of 94%:2%:3%:3%, and evenly mixed using a beater in an aqueous solvent. The battery slurry was coated on a copper foil, dried, cut into pieces, and assembled into button-type half-cells in a glove box, and their electrochemical properties were evaluated.

[0077] The electrochemical test mode is: the first week is 0.1C discharge to 0.005V, 0.05C discharge to 0.005V, 0.02C discharge to 0.005V. After standing for 5s, charge to 1V at 0.1C. The subsequent cycles are 0.5C discharge to 0.005V, 0.2C discharge to 0.005V, 0.05C discharge to 0.005V, 0.02C discharge to 0.005V, and charge to 1V at 0.5C after standing for 5s.

[0078] The discharge in the above electrochemical test is a lithium insertion process, corresponding to the charge in the full battery, and the charge in the above electrochemical test is a lithium removal process, corresponding to the discharge of the full battery.

[0079] After the prepared negative electrode material was coated on copper foil according to the above ratio, a 1Ah soft-pack battery was assembled with lithium cobalt oxide as the positive electrode, and its cycle performance at 0.5C was tested.

[0080] The test results of the first cycle efficiency and 100-cycle capacity retention rate of the half-cell prepared in this embodiment are recorded in Table 1.

[0081] Example 2

[0082] Weigh 15g of carbon nanotube powder and place it in a round-bottom flask. Slowly add concentrated sulfuric acid solution at a solid-liquid ratio of 50mL / g. Perform condensation reflux treatment in a constant temperature oil bath at 90℃ for 12h. Acidification of carbon nanotubes can effectively remove impurities and oxides on the surface of the material and improve the purity of the material. Use a centrifugal speed of 5000rpm and a centrifugal time of 10min to separate the solid and liquid. Then wash the solid carbon nanotube powder with deionized water and ethanol three times. Place the obtained solid in an oven and dry it at 80℃ to obtain acid-treated carbon nanotubes. Weigh 10g of acidified carbon nanotubes and 0.5g of scandium nitrate and disperse them in 1050mL of ethanol solution. Ultrasonicate for 0.5h to mix evenly to obtain a mixed solution. Add 5g of dimethylimidazole to the mixed solution, continue stirring until the reaction is complete, centrifuge at 7000rpm for 10min, collect the precipitate, wash three times with deionized water and ethanol, place the obtained solid in an oven, dry at 80°C to obtain a scandium nitride / carbon nanotube composite material precursor. The precursor is heated to 600°C at a heating rate of 10°C / min in a nitrogen atmosphere, heat treated for 8h, and cooled to room temperature to obtain a scandium nitride / carbon nanotube composite material.

[0083] The obtained negative electrode material was used to prepare negative electrode sheets and button-type half-cells were assembled for testing. The assembly and testing methods were the same as those in Example 1.

[0084] The test results of the first cycle efficiency and 100-cycle capacity retention rate of the half-cell prepared in this embodiment are recorded in Table 1.

[0085] Example 3

[0086] Weigh 15g of carbon nanotube powder and place it in a round-bottom flask. Slowly add concentrated sulfuric acid solution at a solid-liquid ratio of 100mL / g. Perform condensation reflux treatment in a constant temperature oil bath at 100℃ for 11h. Acidification of carbon nanotubes can effectively remove impurities and oxides on the surface of the material and improve the purity of the material. Use a centrifugal speed of 6000rpm and a centrifugal time of 10min to separate the solid and liquid. Then wash the solid carbon nanotube powder with deionized water and ethanol three times. Place the obtained solid in an oven and dry it at 80℃ to obtain acid-treated carbon nanotubes. Weigh 10g of acidified carbon nanotubes and 0.67g of scandium nitrate and disperse them in 213.4mL of ethanol solution. Ultrasonicate for 0.5h to mix evenly to obtain a mixed solution. 3.35 g of dimethylimidazole was added to the mixed solution, and the mixture was stirred continuously until the reaction was complete. The mixture was centrifuged at a centrifugal speed of 5000 rpm for 10 min, and the precipitate was collected and washed three times with deionized water and ethanol. The obtained solid was placed in an oven and dried at 80° C. to obtain a scandium nitride / carbon nanotube composite material precursor. The precursor was heated to 800° C. at a heating rate of 5° C. / min in a nitrogen atmosphere, and heat-treated for 6 h. After cooling to room temperature, a scandium nitride / carbon nanotube composite material was obtained.

[0087] The obtained negative electrode material was used to prepare negative electrode sheets and button-type half-cells were assembled for testing. The assembly and testing methods were the same as those in Example 1.

[0088] The test results of the first cycle efficiency and 100-cycle capacity retention rate of the half-cell prepared in this embodiment are recorded in Table 1.

[0089] Example 4

[0090] Weigh 15g of carbon nanotube powder and place it in a round-bottom flask. Slowly add concentrated sulfuric acid solution at a solid-liquid ratio of 80mL / g. Perform condensation reflux treatment in a constant temperature oil bath at 110℃ for 10.5h. Acidification of carbon nanotubes can effectively remove impurities and oxides on the surface of the material and improve the purity of the material. Use a centrifugal speed of 6500rpm and a centrifugal time of 10min to separate the solid and liquid. Then wash the solid carbon nanotube powder with deionized water and ethanol three times. Place the obtained solid in an oven and dry it at 80℃ to obtain acid-treated carbon nanotubes. Weigh 10g of acidified carbon nanotubes and 1g of scandium sulfate and disperse them in 550mL of ethanol solution. Ultrasonicate for 0.75h to mix evenly to obtain a mixed solution. 8 g of dimethylimidazole was added to the mixed solution, and the mixture was stirred continuously until the reaction was complete. The mixture was centrifuged at a centrifugal speed of 5000 rpm for 10 min, and the precipitate was collected and washed three times with deionized water and ethanol. The obtained solid was placed in an oven and dried at 80°C to obtain a scandium nitride / carbon nanotube composite material precursor. The precursor was heated to 820°C at a heating rate of 4°C / min in a nitrogen atmosphere, and heat treated for 7 hours. After cooling to room temperature, a scandium nitride / carbon nanotube composite material was obtained.

[0091] The obtained negative electrode material was used to prepare negative electrode sheets and button-type half-cells were assembled for testing. The assembly and testing methods were the same as those in Example 1.

[0092] The test results of the first cycle efficiency and 100-cycle capacity retention rate of the half-cell prepared in this embodiment are recorded in Table 1.

[0093] Example 5

[0094] Weigh 15g of carbon nanotube powder and place it in a round-bottom flask. Slowly add concentrated hydrochloric acid solution at a solid-liquid ratio of 50mL / g. Perform condensation reflux treatment in a constant temperature oil bath at 120℃ for 11h. Acidification of carbon nanotubes can effectively remove impurities and oxides on the surface of the material and improve the purity of the material. Use a centrifugal speed of 7500rpm and a centrifugal time of 10min to separate the solid and liquid. Then wash the solid carbon nanotube powder with deionized water and ethanol three times. Place the obtained solid in an oven and dry it at 80℃ to obtain acid-treated carbon nanotubes. Weigh 10g of acidified carbon nanotubes and 0.5g of scandium sulfate and disperse them in 262.5mL of ethylene glycol solution. Ultrasonicate for 0.75h to mix evenly to obtain a mixed solution. 4.5 g of dimethylimidazole was added to the mixed solution, and the mixture was stirred continuously until the reaction was complete. The mixture was centrifuged at 6000 rpm for 10 min, and the precipitate was collected and washed three times with deionized water and ethanol. The obtained solid was placed in an oven and dried at 80° C. to obtain a scandium nitride / carbon nanotube composite material precursor. The precursor was heated to 800° C. at a heating rate of 8° C. / min in a nitrogen atmosphere, and heat-treated for 5 h. After cooling to room temperature, a scandium nitride / carbon nanotube composite material was obtained.

[0095] The obtained negative electrode material was used to prepare negative electrode sheets and button-type half-cells were assembled for testing. The assembly and testing methods were the same as those in Example 1.

[0096] The test results of the first cycle efficiency and 100-cycle capacity retention rate of the half-cell prepared in this embodiment are recorded in Table 1.

[0097] Example 6

[0098] Weigh 15g of carbon nanotube powder and place it in a round-bottom flask. Slowly add concentrated sulfuric acid solution at a solid-liquid ratio of 70mL / g. Perform condensation reflux treatment in a constant temperature oil bath at 100℃ for 11.5h. Acidification of carbon nanotubes can effectively remove impurities and oxides on the surface of the material and improve the purity of the material. Use a centrifugal speed of 6000rpm and a centrifugal time of 10min to separate the solid and liquid. Then wash the solid carbon nanotube powder with deionized water and ethanol three times. Place the obtained solid in an oven and dry it at 80℃ to obtain acid-treated carbon nanotubes. Weigh 10g of acidified carbon nanotubes and 0.8g of scandium sulfate and disperse them in 360mL of ethanol solution. Ultrasonicate for 1h to mix evenly to obtain a mixed solution. 4.8 g of dimethylimidazole was added to the mixed solution, and the mixture was stirred continuously until the reaction was complete. The mixture was centrifuged at 7000 rpm for 10 min, and the precipitate was collected and washed three times with deionized water and ethanol. The obtained solid was placed in an oven and dried at 80° C. to obtain a scandium nitride / carbon nanotube composite material precursor. The precursor was heated to 850° C. at a heating rate of 3° C. / min in a nitrogen atmosphere, and heat-treated for 4 h. After cooling to room temperature, a scandium nitride / carbon nanotube composite material was obtained.

[0099] The obtained negative electrode material was used to prepare negative electrode sheets and button-type half-cells were assembled for testing. The assembly and testing methods were the same as those in Example 1.

[0100] The test results of the first cycle efficiency and 100-cycle capacity retention rate of the half-cell prepared in this embodiment are recorded in Table 1.

[0101] Example 7

[0102] Weigh 15g of carbon nanotube powder and place it in a round-bottom flask. Slowly add concentrated nitric acid solution at a solid-liquid ratio of 120mL / g. Perform condensation reflux treatment in a constant temperature oil bath at 115℃ for 12h. Acidification of carbon nanotubes can effectively remove impurities and oxides on the surface of the material and improve the purity of the material. Use a centrifugal speed of 5000rpm and a centrifugal time of 10min to separate the solid and liquid. Then wash the solid carbon nanotube powder with deionized water and ethanol three times. Place the obtained solid in an oven and dry it at 80℃ to obtain acid-treated carbon nanotubes. Weigh 10g of acidified carbon nanotubes and 0.85g of scandium chloride and disperse them in 135.63mL of ethylene glycol solution. Ultrasonicate for 0.5h to mix evenly to obtain a mixed solution. Add 5.95g of dimethylimidazole to the mixed solution, continue stirring until the reaction is complete, centrifuge at a centrifugal speed of 7000rpm for 10min, collect the precipitate, wash it three times with deionized water and ethanol, place the obtained solid in an oven, and dry it at 80°C to obtain a scandium nitride / carbon nanotube composite material precursor. The precursor is heated to 750°C at a heating rate of 5°C / min in a nitrogen atmosphere, heat treated for 7h, and cooled to room temperature to obtain a scandium nitride / carbon nanotube composite material.

[0103] The obtained negative electrode material was used to prepare negative electrode sheets and button-type half-cells were assembled for testing. The assembly and testing methods were the same as those in Example 1.

[0104] The test results of the first cycle efficiency and 100-cycle capacity retention rate of the half-cell prepared in this embodiment are recorded in Table 1.

[0105] Example 8

[0106] Weigh 15g of carbon nanotube powder and place it in a round-bottom flask. Slowly add concentrated hydrochloric acid solution at a solid-liquid ratio of 50mL / g. Perform condensation reflux treatment in a constant temperature oil bath at 105℃ for 10h. Acidification of carbon nanotubes can effectively remove impurities and oxides on the surface of the material and improve the purity of the material. Use a centrifugal speed of 5000rpm and a centrifugal time of 10min to separate the solid and liquid. Then wash the solid carbon nanotube powder with deionized water and ethanol three times. Place the obtained solid in an oven and dry it at 80℃ to obtain acid-treated carbon nanotubes. Weigh 10g of acidified carbon nanotubes and 0.9g of scandium chloride and disperse them in 218mL of ethylene glycol solution. Ultrasonicate for 0.65h to mix evenly to obtain a mixed solution. 6.3 g of dimethylimidazole was added to the mixed solution, and the mixture was stirred continuously until the reaction was complete. The mixture was centrifuged at 7000 rpm for 10 min, and the precipitate was collected and washed three times with deionized water and ethanol. The obtained solid was placed in an oven and dried at 80°C to obtain a scandium nitride / carbon nanotube composite material precursor. The precursor was heated to 780°C at a heating rate of 2°C / min in a nitrogen atmosphere, and heat-treated for 6 h. After cooling to room temperature, a scandium nitride / carbon nanotube composite material was obtained.

[0107] The obtained negative electrode material was used to prepare negative electrode sheets and button-type half-cells were assembled for testing. The assembly and testing methods were the same as those in Example 1.

[0108] The test results of the first cycle efficiency and 100-cycle capacity retention rate of the half-cell prepared in this embodiment are recorded in Table 1.

[0109] Example 9

[0110] Weigh 15g of carbon nanotube powder and place it in a round-bottom flask. Slowly add concentrated nitric acid solution at a solid-liquid ratio of 120mL / g. Perform condensation reflux treatment in a constant temperature oil bath at 120℃ for 11.5h. Acidification of carbon nanotubes can effectively remove impurities and oxides on the surface of the material and improve the purity of the material. Use a centrifugal speed of 7000rpm and a centrifugal time of 10min to separate the solid and liquid. Then wash the solid carbon nanotube powder with deionized water and ethanol three times. Place the obtained solid in an oven and dry it at 80℃ to obtain acid-treated carbon nanotubes. Weigh 10g of acidified carbon nanotubes and 0.8g of scandium oxalate and disperse them in 720mL of aqueous solution. Ultrasonicate for 1h to mix evenly to obtain a mixed solution. 8 g of ethylenediaminetetraacetic acid was added to the mixed solution, and the mixture was stirred continuously until the reaction was complete. The mixture was centrifuged at 7000 rpm for 10 min, and the precipitate was collected and washed three times with deionized water and ethanol. The obtained solid was placed in an oven and dried at 80°C to obtain a scandium nitride / carbon nanotube composite material precursor. The precursor was heated to 800°C at a heating rate of 5°C / min in a nitrogen atmosphere, and heat treated for 7 hours. After cooling to room temperature, a scandium nitride / carbon nanotube composite material was obtained.

[0111] The obtained negative electrode material was used to prepare negative electrode sheets and button-type half-cells were assembled for testing. The assembly and testing methods were the same as those in Example 1.

[0112] The test results of the first cycle efficiency and 100-cycle capacity retention rate of the half-cell prepared in this embodiment are recorded in Table 1.

[0113] Example 10

[0114] Weigh 15g of carbon nanotube powder and place it in a round-bottom flask. Slowly add concentrated nitric acid solution at a solid-liquid ratio of 95mL / g. Perform condensation reflux treatment in a constant temperature oil bath at 100℃ for 12h. Acidification of carbon nanotubes can effectively remove impurities and oxides on the surface of the material and improve the purity of the material. Use a centrifugal speed of 8000rpm and a centrifugal time of 10min to separate the solid and liquid. Then wash the solid carbon nanotube powder with deionized water and ethanol three times. Place the obtained solid in an oven and dry it at 80℃ to obtain acid-treated carbon nanotubes. Weigh 10g of acidified carbon nanotubes and 0.65g of scandium oxalate and disperse them in 213mL of N,N-dimethylformamide solution. Ultrasonicate for 0.5h to mix evenly to obtain a mixed solution. Add 6.5g of ethylenediaminetetraacetic acid to the mixed solution, continue stirring until the reaction is complete, centrifuge at a centrifugal speed of 7000rpm for 10min, collect the precipitate, wash it three times with deionized water and ethanol, place the obtained solid in an oven, and dry it at 80°C to obtain a scandium nitride / carbon nanotube composite material precursor. The precursor is heated to 850°C at a heating rate of 10°C / min in an argon atmosphere, heat treated for 5.5h, and cooled to room temperature to obtain a scandium nitride / carbon nanotube composite material.

[0115] The obtained negative electrode material was used to prepare negative electrode sheets and button-type half-cells were assembled for testing. The assembly and testing methods were the same as those in Example 1.

[0116] The test results of the first cycle efficiency and 100-cycle capacity retention rate of the half-cell prepared in this embodiment are recorded in Table 1.

[0117] In order to better illustrate the effect of the embodiment of the present invention, a comparative example is compared with the above embodiment.

[0118] Comparative Example 1

[0119] This comparative example provides a preparation process and performance test of a negative electrode material, and the specific preparation process is as follows.

[0120] Weigh 15g of carbon nanotube powder and place it in a round-bottom flask. Slowly add concentrated sulfuric acid solution according to the solid-liquid ratio of 150mL / g. Perform condensation reflux treatment in a constant temperature oil bath at 130℃ for 10h. Acidification of carbon nanotubes can effectively remove impurities and oxides on the surface of the material and improve the purity of the material. Use a centrifugal speed of 8000rpm and a centrifugal time of 10min to separate the solid and liquid. Then wash the solid carbon nanotube powder with deionized water and ethanol three times, place the obtained solid in an oven, and dry it at 80℃ to obtain the acid-treated carbon nanotubes. Heat the above carbon nanotubes to 900℃ at a heating rate of 2℃ / min under a nitrogen atmosphere, heat treat for 2h, and cool to room temperature to obtain the carbon nanotube negative electrode material.

[0121] The obtained negative electrode material was used to prepare negative electrode sheets and button-type half-cells were assembled for testing. The assembly and testing methods were the same as those in Example 1.

[0122] The test results of the first cycle efficiency and 100-cycle capacity retention rate of the half-cell prepared in this comparative example are recorded in Table 1.

[0123] Comparative Example 2

[0124] This comparative example provides a preparation process and performance test of a negative electrode material, and the specific preparation process is as follows.

[0125] Weigh 5g of scandium nitrate and disperse it in 100mL of ethanol solution, mix it evenly by ultrasonic for 1h to obtain a mixed solution. Add 20g of dimethylimidazole to the above mixed solution, continue stirring until the reaction is complete, centrifuge at a centrifugal speed of 8000rpm for 10min, collect the precipitate, wash it three times with deionized water and ethanol, place the obtained solid in an oven, and dry it at 80℃ to obtain a scandium nitride material precursor. The above precursor is heated to 900℃ at a heating rate of 2℃ / min in a nitrogen atmosphere, heat treated for 2h, and cooled to room temperature to obtain a scandium nitride negative electrode material.

[0126] The obtained negative electrode material was used to prepare negative electrode sheets and button-type half-cells were assembled for testing. The assembly and testing methods were the same as those in Example 1.

[0127] The test results of the first cycle efficiency and 100-cycle capacity retention rate of the half-cell prepared in this comparative example are recorded in Table 1.

[0128] Table 1 below shows the electrochemical performance test comparison data of the negative electrode materials prepared in Examples 1-10 and Comparative Examples 1-2.

[0129] Example First week efficiency 100-week capacity retention 1 85.5% 85% 2 85.3% 85% 3 85.2% 84% 4 84.9% 84% 5 84.7% 83% 6 84.5% 83% 7 84.8% 85% 8 83.9% 84% 9 84.1% 83% 10 83.8% 82% Comparative Example 1 75.0% 74% Comparative Example 2 72.2% 57%

[0130] Table 1

[0131] It can be seen from the test data in Table 1 that the first week coulombic efficiency and cycle capacity retention rate of Examples 1-10 are better than those of Comparative Examples 1 and 2. This is because the preparation method of the composite negative electrode material for ion batteries provided in the embodiments of the present invention is easy to control, safe and efficient. The composite material of carbon nanotubes and scandium nitride, on the basis of having excellent electronic conduction and ion transmission capabilities, alleviates electrode polarization, volume expansion effect and voltage hysteresis, and optimizes fast charge and discharge performance and coulombic efficiency. Therefore, the composite negative electrode material for lithium-ion batteries provided by the present invention has excellent electrochemical properties, ideal first coulombic efficiency, cycle stability and safety performance, and has broad application prospects.

[0132] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for preparing a composite negative electrode material for a lithium ion battery, characterized in that: The preparation method comprises: Placing carbon nanotube powder in a flask, adding an acidic solution to acidify the carbon nanotube powder, and performing condensation reflux treatment in a constant temperature oil bath at 90-130° C. to remove impurities and oxides on the surface of the carbon nanotube powder material; performing centrifugal solid-liquid separation on the condensed liquid after the condensation reflux treatment, washing the separated solid powder with deionized water and ethanol respectively, and drying the solid material obtained after washing in an oven to obtain pretreated carbon nanotubes; Weighing the scandium metal salt and the pretreated carbon nanotubes, dispersing them into an organic solvent or water, and uniformly mixing them by ultrasonication to obtain a mixed solution; Adding an organic ligand to the mixed solution and continuously stirring until the reaction is complete, collecting a precipitate by centrifugal solid-liquid separation, washing the precipitate with deionized water and ethanol respectively, and drying the solid material obtained after washing in an oven to obtain a scandium nitride / carbon nanotube composite material precursor; wherein the organic ligand comprises at least one of dimethylimidazole, ethylenediaminetetraacetic acid or ethylenediamine; The scandium nitride / carbon nanotube composite material precursor is subjected to high temperature heat treatment at 600° C.-900° C. in an inert atmosphere, and after cooling to room temperature, a scandium nitride / carbon nanotube composite material is obtained, which is the lithium ion battery composite negative electrode material.

2. The preparation method according to claim 1, characterized in that: The acidic solution includes one or more of concentrated nitric acid, concentrated hydrochloric acid, and concentrated sulfuric acid; The liquid-to-solid ratio of the acidic solution to the carbon nanotubes is 50-150 mL / g.

3. The preparation method according to claim 1, characterized in that: The condensation reflux treatment time is 10-12h.

4. The preparation method according to claim 1, characterized in that: The rotation speed of the centrifugal solid-liquid separation is 5000rpm-8000rpm, and the time is 10min; The washing with deionized water and ethanol respectively specifically includes: washing with ethanol and deionized water alternately three times.

5. The preparation method according to claim 1, characterized in that: The scandium metal salt includes: one or more of scandium chloride, scandium nitrate, scandium sulfate, scandium oxalate and hydrates thereof; The mass ratio of the scandium metal salt to the pretreated carbon nanotubes is 1:10-1:20; The organic solvent includes: at least one of methanol, ethanol, ethylene glycol, and N,N-dimethylformamide; The ratio of the total mass of the scandium metal salt and the pretreated carbon nanotubes to the volume of the organic solvent or water is 1 g / 100 mL to 10 g / 100 mL; The ultrasonic time is 0.5-1h.

6. The preparation method according to claim 1, characterized in that: The mass ratio of the scandium metal salt to the organic ligand is 1:4-1:

10.

7. The preparation method according to claim 1, characterized in that: The inert atmosphere is nitrogen or argon; During the heating process of the high-temperature heat treatment, the heating rate is 2°C / min-10°C / min; and the heat treatment time is 2h-8h.

8. A lithium-ion battery composite negative electrode material prepared by the preparation method according to any one of claims 1 to 7.

9. A negative electrode plate for a lithium battery, characterized in that: The lithium battery negative electrode plate comprises the lithium ion battery composite negative electrode material as described in claim 8 above.

10. A lithium battery, characterized in that: The lithium battery comprises the lithium battery negative electrode plate as described in claim 9 above.